Substrate Bias Voltage Tailoring the Interfacial Chemistry of a-SiCₓ:H: A Surprising Improvement in Adhesion of a-C:H Thin Films Deposited on Ferrous Alloys Controlled by Oxygen - Crespi, ngela E; Leidens, Leonardo M.; Antunes, Vinícius; Perotti, Bruna L; Michels, Alexandre F; Alvarez, Fernando; Figueroa, Carlos A. (ACS applied materials & interfaces, 2019)
Hydrogenated amorphous carbon thin films (a-C:H) have attracted much attention because of their surprising properties, including ultralow friction coefficients in specific conditions. Adhesion of a-C:H films on ferrous alloys is poor due to chemical and physical aspects, avoiding a widespread application of such a film. One possibility to overcome this drawback is depositing an interlayer—an intermediate thin film—between the carbon-based coating and the substrate to improve chemical interaction and adhesion. Based on this, interlayers play a key role on a-C:H thin-film adhesion through a better chemical network structure at the outermost layer of the a-SiCₓ:H interlayer, i.e., the a-C:H/a-SiCₓ:H interface. However, despite the latest important advances on the subject, the coating adhesion continues being a cumbersome problem since it depends on multifactorial causes. Thus, the purpose of this paper is to report a standard protocol leading to surprising good results based on the control of the interfacial chemical bonding by properly biasing the substrate (between 500 and 800 V) during the a-SiCₓ:H interlayer deposition at an appropriate low temperature, by using hexamethyldisiloxane as precursor. The interlayers and the outermost interfaces were analyzed by a comprehensive set of techniques, including X-ray photoelectron spectroscopy, glow discharge optical emission spectroscopy, and Fourier transform infrared spectroscopy. Nanoscratch tests, complemented by scanning electron microscopy and energy-dispersive X-ray spectroscopy, were used to evaluate the critical load for delamination to certify and quantify the adhesion improvement. This study was important to identify the chemical local bonding of the elements at the interface and its local environment, including the in-depth chemical composition profile of the coating. An important effect is that the oxygen content decreases on increasing substrate bias voltage, improving the adhesion of the film. This is due to the fact that energetic ion hitting the growing interlayer breaks Si–O and C–O bonds, augmenting the content of Si–C and C–C bonds at the outermost interface of the a-SiCₓ:H interlayer and enhancing the a-C:H coating adhesion. Moreover, the combination of high bias voltage (800 V) and low temperature (150 °C) during the a-SiCₓ:H interlayer deposition allows good adhesion of a-C:H thin films due to sputtering of light elements like oxygen. Therefore, an appropriated bias and temperature combination can open new pathways in a-C:H thin-film deposition at low temperatures. These results are particularly interesting for temperature-sensible metal alloys, where well-adhered a-C:H thin films are mandatory for tribological applications.